(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The subject of this research paper revolves around the crisis of theory in media and communication sciences in the era of big data, where the concept of knowledge has changed from understanding and interpretation to prediction and measurement, and data has become presented as an alternative to theory. Focusing on the fact that this transformation has created three interconnected crises: a methodology dominated by logic “data first”, a cognitive approach that excludes human meaning and context, and an ideology that claims the neutrality of data despite its service to systems of power and the economy. The article also proposes to overcome this crisis through a hybrid approach that combines quantitative and critical analysis, and the development of new concepts such as algorithmic culture, graphic colonialism, and surveillance capitalism This restores the theory’s role as a critical tool that reveals the power relations underlying algorithms and preserves the human and cognitive character in a world governed by data.